Alopecia areata/Congenital triangular alopecia. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Congenital triangular alopecia consists of a patch seemingly devoid of hair, often localized on the front parietal region, isosceles triangle-shaped with front base, present from the first age and lasting with time. Early onset, long persistence and approximatively elongated shape are reminiscent of a nevus. Its less known name is really Brauer nevus (1). Some Authors (2) showed that the seemingly alopecic area of congenital triangular alopecia has really a normal density of hairs, although we are dealing with very thin vellus hairs. This disorder should be differentiated from alopecia areata.